Analysis of genetic relationship on Amygdalus mira (koehne) Ricker with other peach species using simple sequence repeat (SSR). (October 2015) - Peng, Mu; Guan, Fachun; Tao, Lei; Li, Rongqin; Wang, Chao; Meng, Fanjuan
Abstract: Amygdalus mira (Koehne) Ricker is native to China and has many good economical traits. However, its genetic diversity information has not been extensively studied. In this study, to assess the genetic diversity and relationships of A . mira and other peach species (nineteen accessions from Zhengzhou, Henan Province and seven accessions from Harbin) we used simple sequence repeat (SSR) markers. Here, 10 SSR primers were used, and 100% of the SSR primers were polymorphic, with an average of 5.5 alleles per primer pairs, suggesting that these primers were informative for this study. Additionally, polymorphism information content (PIC) value ranged from 0.82 to 0.96 with an average of 0.91. All the accessions were clustered into two groups (cluster 1 and cluster 2) based on SSR data. Principal coordinate analysis recovered similar results that all accessions were divided into two major clusters. The genetic variations within and among populations were 63.9% and 36.1%, respectively. In conclusion, A . mira maintains high genetic variation levels. This research will be potentially useful to aid breeding and enhance the economic and ornamental value of this wild peach. Highlights: Amygdalus mira koehne maintain high levels of genetic variation based on SSR technique. SSR technique was used to detect the genetic diversity of the A . mira koehne germplasm. The relationship of A . mira koehne with other peach species was analyzed. Information will be useful to enhance the economic and ornamental value of A. mira koehne.